Sector de la construcción : evaluación de guantes de protección contra riesgos mecánicos fabricados en el Perú - Cira Reneé Bringas-Masgo; Carolina Ullilen-Marcilla (Universidade do Porto, 2020)
In the construction industry, gloves provide an important first barrier to protect workers' hands. This study focuses on the evaluation of the design of leather gloves made in Peru against mechanical risks. For this purpose, 16 types of leather gloves were chosen to go through the process of testing their levels of performance in terms of abrasion, tear and puncture resistance under the norm UNE EN 388 :2016 + A1 :2018. In addition to this, 80 Peruvian construction workers were the subject of an anthropometric study by filling a questionnaire to understand their perception of the gloves used in the evaluation. In addition, we conducted an interview with a proper manufacturer of gloves. In conclusion, the gloves used in this study offer less protection in terms of abrasion resistance, are generally made in one-size-to-fit-all and the handling of bricks causes them to quickly wear out.